Carotid Disease and Ageing: A Literature Review on the Pathogenesis of Vascular Senescence in Older Subjects. (13th June 2020) - Sertedaki, Eleni; Veroutis, Dimitris; Zagouri, Flora; Galyfos, George; Filis, Konstadinos; Papalambros, Alexandros; Aggeli, Konstantina; Tsioli, Panagiota; Charalambous, George; Zografos, George; Sigala, Fragiska
Abstract : Aging is a natural process that affects all systems of the human organism, leading to its inability to adapt to environmental changes. Advancing age has been correlated with various pathological conditions, especially cardiovascular and cerebrovascular diseases. Carotid artery (CA) is mainly affected by age-induced functional and morphological alterations causing atheromatous disease. The evolvement of biomedical sciences has allowed the elucidation of many aspects of this condition. Symptomatic carotid disease (CD) derives from critical luminar stenosis or eruption of an atheromatous plaque due to structural modifications of the vessels, such as carotid intima-media thickening. At a histologic level, the aforementioned changes are mediated by elastin fragmentation, collagen deposition, immune cell infiltration, and accumulation of cytokines and vasoconstrictors. Underlying mechanisms include chronic inflammation and oxidative stress, dysregulation of cellular homeostatic systems, and senescence. Thus, there is an imbalance in components of the vessel wall, which fails to counteract exterior stress stimuli. Consequently, arterial relaxation is impaired and atherosclerotic lesions progress. This is a review of current evidence regarding the relationship of aging with vascular senescence and CD. A deeper understanding of these mechanisms can contribute to the production of efficient prevention methods and targeted therapeutic strategies.